Pengaruh Dimensi Kredibilitas Influencer: Attractiveness, Trustworthiness Dan Expertise Terhadap Niat Membeli Pada Produk "Safi-Skincare" - Muhammad Rifan Jungki Dausat; Muchsin Muthohar (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This study aims to identify the influence of credibility dimensions (attractiveness, trustworthiness and expertise) of influencers on intention to buy on "Safi-Skincare" products. The type of data used is primary data, which refers to information obtained directly from research subjects through measurement tools or data collection methods. In this study, we obtained data by circulating questionnaires to 250 respondents aged 16 to 35 years, and then this data was analyzed using Statistical Package for the Social Sciences (SPSS) software. The results of this research analysis show that there is a positive and significant influence between the dimensions of credibility (attractiveness and expertise) of an influencer on purchase intention, except for the dimension of trust in influencer credibility. There is a positive and significant influence between the dimensions of credibility (attractiveness, trustworthiness and expertise) of an influencer on online customer engagement. There is a positive and significant influence between online customer engagement and purchase intention. This research has the potential to be expanded to present greater variation and increase the validity of existing theories. This can be achieved through the development of research objects, increasing the number of respondents, more in-depth research on various aspects of influencer credibility dimensions, as well as more detailed research on the influence of influencer credibility.